Phytochemicals, antibacterial and cytotoxic activities of Nerium oleander L. (Bangladesh Journal of Botany, 2025)
Nerium oleander L. is used as conventional medicine for the management of various diseases. This investigation looked into the toxicity, antibacterial and phytochemical profiles of N.  oleander leaf extract. Different concentrations of N. oleander methanolic leaf extract were applied to Vero and HeLa cells to determine the cytotoxic activity of the plant. The Cell Titer 96 Non-Radioactive Cell Proliferation Assay Kit (Promega, USA) was used to assess the viability of the cells. After 48 h, LD50 values of the methanolic extract were determined to be LD50 of 9 mg/ml against Vero cell and 46.5 mg/ml on HeLa cell, respectively. The present investigation showed the potential cytotoxic effect of N. oleander extract on Vero cells and anti-cancerous effects on HeLa cells through the induction of death cells. The antibacterial activity of Staphylococcus aureus, Pseudomonas aeruginosa, Salmonella typhi, and Bacillus subtilis showed inhibition zones of 10, 8, 7, and 2 mm, respectively. The results of the investigation showed that leaves of N. oleander contain tannins, reducing sugar, glycosides, and terpenoids.Bangladesh J. Bot. 54(1): 99-104, 2025 (March)